Informal Employment : Safety Net or Growth Engine? - Loayza, Norman V.; Rigolini, Jamele (2012)
Is informal employment a safety net or a growth engine? To address this question, this paper studies the trends and cycles of informal employment. It first presents a theoretical model of long- and short-run behavior of informal labor. Then it analyzes these relationships empirically, using the share of self-employment in the labor force as the proxy for informal employment. In the long run, informality is larger when labor productivity is lower, government services weaker, and business flexibility less prevalent. In the short run, informal employment behaves counter-cyclically, indicating that it acts primarily as a safety net. The degree of counter-cyclicality, however, varies inversely with the size of informal labor itself.